Environmentally Sustainable Food Systems for Food Security and Nutrition - Arunachalam, A.; Ayyappan, S. (Indian Farming, 2015)
India has large number of small and marginal farming community, where the size of land holding is very low to achieve the standards of livelihood. Major population lives in villages and their principal source of livelihood is agriculture, comprising crop and animal husbandry, forestry, fisheries, agro-processing and agribusiness. Therefore, accelerated progress in enhancing the productivity, profitability, stability, and sustainability of the major farming systems is the best safety net against hunger and poverty. Realizing the potential of agriculture-based livelihoods, development of entrepreneurial skills to promote secondary agriculture could be vital for sustainable socio-economic development of small and marginal farmers. Further, the nutritional aspects of food habits needs special attention as there is a threat of malnutrition globally and in particular in the Indian sub-continent. Thus, the National Nutrition Policy has to be reconciled with the Food Security to improve the conditions of food and nutritional security in the country.